LITERASI DIGITAL SEBAGAI PENGUATAN BARGAINING POSITION PRODUK KREATIF DALAM PEMBERDAYAAN KELOMPOK PEREMPUAN “MOSS 1” - Indah Ibanah; Rizky Yanuarti; Lenny Luthfiyah; Laily Mutmainnah (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2022)
Mother School Sumbersari (MOSS) 1 is an assisted group of Kantor urusan Agama (KUA) dan Penyuluh Sumbersari in Sumbersari district, Jember Regency. MOSS 1 studies about entrepreneurship as one of their’s activities. The member of MOSS 1 produce food and beverage products during routine events and sell the product by whatsapp. Another activites carried out such as knitting, make a bead and creating another product. MOSS 1 have problems with product marketing and branding. Therefore, the aims of this community service activities are training in making-digital brochures and stengthening branding. The methode used are (1) counseling, (2) training, (3) discussion, and (4) evaluation. The results are counseling activities discussing about the importance of digital marketing and branding, brands and logos. The selected training activity is making online brochures. It’s caused the member’s posts on social media are considered as spam, specifically on whatsapp. Online brochures that have been made can be found at the following link https://imooji.com/stage/v5/29NEB/94817. Strengthening the branding of business product is considered very important based on the results of discussion and evaluation. Strengthening creative product business management in MOSS 1 can be used as a recommendation for further PkM activities.